Detection and Genetic Diversity of Porcine Coronavirus Involved in Diarrhea Outbreaks in Spain - Puente, Héctor; Argüello, Héctor; Mencía-Ares, Óscar; Gómez-García, Manuel; Rubio, Pedro; Carvajal, Ana (Frontiers in Veterinary Science, 2021)
Porcine enteric coronaviruses include some of the most relevant viral pathogens to the swine industry such as porcine epidemic diarrhoea virus (PEDV) or porcine transmissible gastroenteritis virus (TGEV) as well as several recently identified virus such as swine enteric coronavirus (SeCoV), porcine deltacoronavirus (PDCoV) or swine enteric alphacoronavirus (SeACoV). The aim of this study is the identification and characterization of enteric coronaviruses on Spanish pig farms between 2017 and 2019. The study was carried out on 106 swine farms with diarrhoea outbreaks where a viral aetiology was suspected by using two duplex RT-PCRs developed for the detection of porcine enteric coronaviruses. PEDV was the only coronavirus detected in our research (38.7% positive outbreaks, 41 out of 106) and neither TGEV, SeCoV, PDCoV nor SeACoV were detected in any of the samples. The complete S-gene of all the PEDV isolates recovered were obtained and compared to PEDV and SeCoV sequences available in GenBank. The phylogenetic tree showed that only PEDV of the INDEL 2 or G1b genogroup has circulated in Spain between 2017-2019. Three different variants were detected, the recombinant PEDV-SeCoV being the most widespread. These results show that PEDV is a relevant cause of enteric disorders in pigs in Spain while new emerging coronavirus have not been detected so far. However, the monitoring of these virus is advisable to curtail their emergence and spread.